The influence of product quality and online shopping experience on customer loyalty through customer satisfaction with Azarine sunscreen products - Deykha Aguilika; Nabila Padmasari (Jurnal STEI Ekonomi, 2026)
Increasing public awareness of the importance of protecting skin from ultraviolet (UV) rays has driven demand for sunscreen products, including in Indonesia. Azarine, a local brand, dominates the e-commerce market with significant sales. This study aims to analyse the influence of product quality and online shopping experience on customer loyalty, with customer satisfaction as a mediating variable. The method employed was a quantitative approach with a purposive sampling technique, involving 100 female students from Trunojoyo University, Madura, who had purchased Azarine sunscreen products online. Data collection was conducted through questionnaires, and data analysis used the Structural Equation Modelling–Partial Least Squares (SEM-PLS) technique using SmartPLS 4.1 software. The results showed that product quality and online shopping experience had a positive and significant effect on customer satisfaction. In addition, both variables also had a direct and indirect effect on customer loyalty through customer satisfaction. Customer satisfaction proved to be a significant mediating variable in shaping customer loyalty. These findings emphasise the importance of strategies to improve product quality and strengthen the digital shopping experience as steps to build and maintain customer loyalty, especially in the increasingly competitive skincare industry.